2012
DOI: 10.4161/cam.20879
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of periostin in excisional skin repair

Abstract: Commentary to: Elliott CG, Wang J, Guo X, Xu SW, Eastwood M, Guan J, et al. Periostin modulates myofibroblast differentiation during full-thickness cutaneous wound repair. J Cell Sci 2012; 125:121-32; PMID:22266908; http://dx.doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In recent years, the role of matricellular proteins in skin healing in mice has been well described [1,9,17], but only one previous study has investigated any of the matricellular proteins in the context of human nonhealing skin wounds; our group demonstrated an inverse correlation between expression of galectin-3 and advanced glycation end product localization [20]. In this study, we assessed the expression, localization and regulation of the profibrotic molecules periostin and CCN2 in tissue isolated from human non-healing skin wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the role of matricellular proteins in skin healing in mice has been well described [1,9,17], but only one previous study has investigated any of the matricellular proteins in the context of human nonhealing skin wounds; our group demonstrated an inverse correlation between expression of galectin-3 and advanced glycation end product localization [20]. In this study, we assessed the expression, localization and regulation of the profibrotic molecules periostin and CCN2 in tissue isolated from human non-healing skin wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Both periostin and CCN2 first appear in the granulation tissue at day 3 as TNFα levels decline and the profibrotic TGF-β1 increases; both periostin and CCN2 are upregulated by TGF-β1 [7,8]. We have previously demonstrated that periostin modulates myofibroblast differentiation (characterized by the expression of α-smooth muscle actin (α-SMA)) in a β1-integrin and focal adhesion kinase-dependent mechanism [9,10]. Furthermore, periostin increases myofibroblast differentiation in low-tension environments such as that associated with developing granulation tissue [10].…”
Section: Introductionmentioning
confidence: 96%
“…The role of Postn in skin pathologies (Arima, et al, 2015, Crawford, et al, 2015, Mineshige, et al, 2015, Shiraishi, et al, 2012, Song and Qin, 2008, Supp, et al, 2012, Yamaguchi, et al, 2013, Zhang, et al, 2015, Zhou, et al, 2010) and wound healing (Elliott, et al, 2012a, Elliott, et al, 2012b, Jackson-Boeters, et al, 2009, Nishiyama, et al, 2011, Ontsuka, et al, 2012, Walker, et al, 2015, Zhou, et al, 2010) has been the subject of intense research, which has pointed to very specific roles for Postn.…”
Section: Skin Healingmentioning
confidence: 99%
“…Postn, like most MPs, is most noticeably re-expressed as a result of tissue injury, temporally and spatially regulating different aspects of the repair process by modifying cell behavior (Walker, et al, 2015). In this review, we will focus on the role of Postn in the healing of skin and cardiac muscle, the two tissue systems where it has been most intensely investigated and its actions defined (Dorn, 2007, Elliott, et al, 2012a). Additionally, we will discuss Postn in tissues where it is known to play prominent roles in development and disease, and although described, its role in repair is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…As we have previously highlighted, in analyzing MPs in skin healing, the devil appears to be in the detail. 83 When considering these two papers on SPARC alone, different wound sizes were used and methods of analysis were not the same. If we focus on analysis of SPARC-null and WT fibroblast migration, standardized methods were not followed in both papers.…”
Section: Proliferative Phase: Crossroads Of Myofibroblasts and Ecm Fomentioning
confidence: 99%